2001
DOI: 10.1128/iai.69.7.4528-4535.2001
|View full text |Cite
|
Sign up to set email alerts
|

Brucella abortus Cyclic β-1,2-Glucan Mutants Have Reduced Virulence in Mice and Are Defective in Intracellular Replication in HeLa Cells

Abstract: Null cyclic ␤-1,2-glucan synthetase mutants (cgs mutants) were obtained from Brucella abortus virulent strain 2308 and from B. abortus attenuated vaccinal strain S19. Both mutants show greater sensitivity to surfactants like deoxycholic acid, sodium dodecyl sulfate, and Zwittergent than the parental strains, suggesting cell surface alterations. Although not to the same extent, both mutants display reduced virulence in mice and defective intracellular multiplication in HeLa cells. The B. abortus S19 cgs mutant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
116
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(120 citation statements)
references
References 35 publications
(36 reference statements)
2
116
1
1
Order By: Relevance
“…No change in colony morphology or change in sensitivity towards bile salts was observed for strain SG111 (Fig S1a). OPG synthesis in Brucella sp., which are nonmotile, is not under osmotic control, but a defect in the opgG gene results in increased sensitivity to surfactants (SDS and deoxycholic acid) (Arellano-Reynoso et al, 2005;Briones et al, 2001), indicating cell-surface alterations, a phenotype also not observed in strain SG111 (Fig S2b). The other significant component of Gram-negative bacteria, the enterobacterial common antigen, has been proposed to play an important role in virulence by protecting the pathogen from bile salts (Ramos-Morales et al, 2003).…”
Section: Discussionmentioning
confidence: 94%
“…No change in colony morphology or change in sensitivity towards bile salts was observed for strain SG111 (Fig S1a). OPG synthesis in Brucella sp., which are nonmotile, is not under osmotic control, but a defect in the opgG gene results in increased sensitivity to surfactants (SDS and deoxycholic acid) (Arellano-Reynoso et al, 2005;Briones et al, 2001), indicating cell-surface alterations, a phenotype also not observed in strain SG111 (Fig S2b). The other significant component of Gram-negative bacteria, the enterobacterial common antigen, has been proposed to play an important role in virulence by protecting the pathogen from bile salts (Ramos-Morales et al, 2003).…”
Section: Discussionmentioning
confidence: 94%
“…Although we cannot draw a conclusion about the exact release mechanism, the linear nature of C. jejuni fOS most likely excludes the mechanism known from cyclic glucan synthesis in other Proteobacteria that was suggested to be coupled to cyclization (10,35). The absence of a eukaryotic PNGaseF-like protein that would release fOS in C. jejuni, and the absence of a gene encoding a pyrophosphatase homolog protein (36) favors a mechanism proposed for the eukaryotic OTase that, in the absence of sufficient acceptor sequences, the OTase exhibits hydrolytic activity and transfers OSs from their lipid-linked intermediates to water (15,16).…”
Section: Discussionmentioning
confidence: 99%
“…While these glycans are comprised exclusively of glucose, they can be structurally diverse, and four distinct families were defined based on variations in chain length, glycosyl linkage, branching pattern, and presence of modifications (1). In addition, periplasmic glucans were reported to be important for biofilm development (3), antibiotic resistance (4), host-pathogen and plant-microbe interactions (5)(6)(7)(8)(9), as well as intracellular multiplication (10). Free oligosaccharides (fOS) have also been described in mammalian cells, yeast, plants, and fish (11).…”
mentioning
confidence: 99%
“…Brucella controls the maturation of its vacuole to avoid innate immune host cell responses, such as lysosome fusion, and to reach its replicative niche (19). B. abortus C␤G-deficient mutants are unable to prevent phagosome-lysosome fusion and are significantly defective in intracellular multiplication in professional and nonprofessional phagocytic cells (7,9). C␤G play a major role in circumventing host cell defense by interacting with cholesterol and reorganizing lipids rafts of host cell membranes (9).…”
Section: Discussionmentioning
confidence: 99%
“…Cyclic ␤-1,2-glucan synthase (Cgs), the enzyme responsible for the synthesis of cyclic ␤-1,2-glucans (C␤G), is present in a restricted number of symbiotic or pathogenic bacteria, most of them belonging to the ␣-proteobacteria group, in which C␤G are a symbiotic or virulence factor required for successful host interaction (4)(5)(6)(7)(8)(9). Brucella abortus Cgs is a 320-kDa (2,867 amino acid residues) polytopic integral inner membrane protein with six transmembrane-spanning segments (TMSs) and with the N and C termini located on the cytoplasmic side of the membrane (10).…”
mentioning
confidence: 99%